Penerapan Model Discovery Learning Berbantuan Media Mind Mapping Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Parhannudin, Parhannudin; Gumilar, Rendra; Srigustini, Astri (Civiliza Publishing, Indonesia., 2023)
This research stems from the issue of low critical thinking skills among students, based on the results of observations and preliminary research. The purpose of this research is to determine the influence of the Discovery Learning model aided by mind mapping media in enchancing students’ critical thinking skill in the subject of international trade concepts in economics. This research employs an experimental method with a quasi-experimental design using non-equivalent control group design. Data collection techniques include essay tests and interviews with students. Based on the research results, it is explained that there is an influence ot the discovery learning model by mind mapping media on students’ critical thinking skills in the subject of international trade concepts in economics. The alternative hypothesis (Ha) is accepted if the significance value (2-tailed) is less than 5% or 0.005, and abused on the research results, the obtained signification value (2-tailed) in 0.000, which is less than 0.05. The average score of the experimental group is higher than the control group, with a score of 83.14 > 79.51. Therefore, it can be concluded from this study that the discovery learning model aided by mind mapping media can enhance students’ critical thinking skills.